AN ANALYSIS WASHBACK AUTHORITY OF STANDARDIZED EDUCATIONAL TESTS ON ENGLISH LANGUAGE INSTRUCTIONS - Indrawati, Lala Nining; Agustina, Yulia; Arfah, Hajriana; Usuluddin (FKIP Unismuh Makassar, 2024)
Standardized evaluations are a widely used tool in education and assessment. These evaluations are carefully designed to present uniform questions and instructions to all participants, ensuring consistent measurement of a student’s knowledge or skills in a specific area. They play a crucial role in assessing and enhancing students’ proficiency in the English language. Hence The purpose of this study is to examine the washback effect of standardized testing in the English language subject. The researcher employed a descriptive qualitative method, utilizing a sample of 10 eighth-semester students majoring in English and 3 lecturers at Hamzanwadi University. The sampling technique used was random sampling, while data collection methods included observation, interviews, and documentation. The findings of this study reveal that standardized tests have a significant impact on the teaching and learning process. These tests often create pressure for both students and teachers, which can lead to stress and anxiety during examinations. Additionally, they can inhibit creativity in teaching methods and result in students struggling to understand the material. Consequently, students may become focused solely on passing exams rather than genuinely comprehending the subject matter. Further elaboration on these points is discussed in detail in the following discussion section